The Effectiveness of Tpack-Based Learning Physics with The PBL Model to Improve Students' Critical Thinking Skills - Wardani, Cindy Adelia; Jatmiko, Budi (International Journal of Active Learning, 2021)
Critical thinking skills are thinking skills that are needed to live in the 21st century. This study aims to analyze the effectiveness of TPACK based physics learning with the PBL model to improve students' critical thinking skills. The research is a Pre-Experimental Design with the trial design a one-group pretest-posttest design. The subjects in this study were students of class X IPA 5 and X IPA 6 SMA Negeri 1 Driyorejo Gresik in the academic year 2020-2021. Trial design using. The data analysis technique used quantitative and interferential descriptive analysis. The results showed that physics learning based on TPACK with the PBL model was effective in improving students' critical thinking skills. In terms: a) improving critical thinking skills of students is significant at ÃŽÂ± = 0.05 (2-tailed), b) mean n-gain score with high category, and c) nothing different in improving critical thinking skills of students at each class. Thus, TPACK-based physics learning with the PBL model can use as input for teachers to improve the critical thinking skills of students.